NG2/CSPG4 attenuates motility in mandibular fibrochondrocytes under serum starvation conditions - Ahn, Shin Young; Bagheri Varzaneh, Mina; Zhao, Yan; Rozynek, Jacob; Ravindran, Sriram; Banks, Jonathan; Chaudhry, Minahil; Reed, David A. (Frontiers in Cell and Developmental Biology, 2023)
The migration of mandibular fibrochondrocytes is important for both the development of the mandible, the homeostasis of mandibular cartilage, and for the capacity of the tissue to respond to injury. Mandibular fibrochondrocytes have to overcome formidable obstacles during migration including a dense and heterogeneous three-dimensional matrix. Guiding the direction of cell migration and commitment to a migratory phenotype in this microenvironment necessitates a multivalent response to chemotactic and extracellular matrix mediated stimuli. One of the key matrix components in the cartilage of the temporomandibular joint is type VI collagen. Neuron/Glial antigen 2 (NG2/CSPG4) is a transmembrane proteoglycan that binds with collagen VI and has been implicated in a wide range of cell behaviors including cell migration, motility, adhesion, and proliferation. While NG2/CSPG4 has been shown to be a key regulator of mandibular cartilage homeostasis, its role in the migration of mandibular fibrochondrocytes during normal and cell stress conditions has yet to be resolved. Here we address this gap in knowledge by characterizing NG2/CSPG4 dependent migration in mandibular fibrochondrocytes using primary mandibular fibrochondrocytes isolated from control and full length NG2/CSPG4 knockout mice, in primary mandibular fibrochondrocytes isolated from NG2|DSRed reporter mice, and in an immortalized mandibular fibrochondrocyte cell line with mutated NG2/CSPG4 ectodomain. All three cells demonstrate similar results, with loss of the full length or truncated NG2/CSPG4 increasing the rate of cell migration in serum starvation/cell stress conditions. These finding clearly implicate NG2/CSPG4 as a key molecule in the regulation of cell migration in mandibular fibrochondrocytes in normal and cell stress conditions, underscoring the role of NG2/CSPG4 as a mechanosensitive signaling hub in mandibular cartilage.